Postprandial changes in cardiometabolic disease risk in young Chinese men following isocaloric high or low protein diets, stratified by either high or low meal frequency - a randomized controlled crossover trial. Issue 1 (December 2015) - Mok, Alexander; Haldar, Sumanto; Lee, Jetty; Leow, Melvin; Henry, Christiani
Abstract Background Cardio-Metabolic Disease (CMD) is the leading cause of death globally and particularly in Asia. Postprandial elevation of glycaemia, insulinaemia, triglyceridaemia are associated with an increased risk of CMD. While studies have shown that higher protein intake or increased meal frequency may benefit postprandial metabolism, their combined effect has rarely been investigated using composite mixed meals. We therefore examined the combined effects of increasing meal frequency (2-large vs 6-smaller meals), with high or low-protein (40 % vs 10 % energy from protein respectively) isocaloric mixed meals on a range of postprandial CMD risk markers. Methods In a randomized crossover study, 10 healthy Chinese males (Age: 29 ± 7 years; BMI: 21.9 ± 1.7 kg/m2 ) underwent 4 dietary treatments: CON-2 (2 large Low-Protein meals), CON-6 (6 Small Low-Protein meals), PRO-2 (2 Large High-Protein meals) and PRO-6 (6 Small High-Protein meals). Subjects wore a continuous glucose monitor (CGM) and venous blood samples were obtained at baseline and at regular intervals for 8.5 h to monitor postprandial changes in glucose, insulin, triglycerides and high sensitivity C-reactive protein (hsCRP). Blood pressure was measured at regular intervals pre- and post- meal consumption. Urine was collected to measure excretion of creatinine and F2 -isoprostanes and its metabolites over the 8.5 h postprandial period. Results The high-protein meals, irrespective of meal frequency were beneficial for glycaemic health since glucose incremental area under the curve (iAUC) for PRO-2 (185 ± 166 mmol.min.L−1 ) and PRO-6 (214 ± 188 mmol.min.L−1 ) were 66 and 60 % lower respectively (bothp < 0.05), compared with CON-2 (536 ± 290 mmol.min.L−1 ). The iAUC for insulin was the lowest for PRO-6 (13.7 ± 7.1 U.min.L−1 ) as compared with CON-2 (28.4 ± 15.6 U.min.L− 1), p  < 0.001. There were no significant differences in postprandial responses in other measurements between the dietary treatments. Conclusions The consumption of composite meals with higher protein content, irrespective of meal frequency appears to be beneficial for postprandial glycemic and insulinemic responses in young, healthy Chinese males. Implications of this study may be useful in the Asian context where the consumption of high glycemic index, carbohydrate meals is prevalent. Trial registration NCT02529228 .